Incidencia del incremento patrimonial no justificado en ingresos de personas que emiten recibo por honorarios, ciudad de Trujillo año 2017 - Rodríguez Meléndez, Analit (2020)
The main objective of this research was to determine the incidence of the unjustified equity increase in income of people who issue a receipt for fees, city of Trujillo in 2017, for which the non-experimental - correlational design with a quantitative approach was used; as well as the following methods: i) Inductive-Deductive, ii) Analytical-Systemic and iii) Exegetical. After the analysis carried out on the data obtained from the survey applied to the people who issued a receipt for fees in the city of Trujillo in the year 2017, there is sixty-eight percent of these people who do not know what the increase in assets is not justified; Their income was basically framed in the exercise of a profession, the most outstanding being that of an accountant and the changes generated by the determination of the unjustified increase in their income are the increase in the tax payable and the decrease in the income of the people who issue a receipt for fees. Therefore, it was determined that the unjustified increase in equity negatively affects the income of people who issue a receipt for fees, city of Trujillo in 2017; since, the determination of unjustified equity increase, generated an increase in the tax payable, which became an additional expense and therefore decreased the income for said year, regardless of whether the audit is from previous years.